Homogenous Metamaterial Description of Localized Spoof Plasmons in Spiral Geometries - Liao, Zhen (2017)
It has been recently shown that ultrathin spiral metamaterials can support localized spoof plasmon modes whose resonant wavelength is much larger than the size of the structure. Here, an analytical model is developed to describe the electromagnetic properties of the two-dimensional version of these devices: a perfect conducting wire corrugated by spiral grooves. The emergence of localized spoof plasmons in this geometry is quantitatively investigated. Calculations show that these modes can be engineered through the spiral angle and the number of grooves. The theory also allows us to elucidate the contribution of magnetic and electric localized spoof plasmons to the optical response of these metamaterial devices. Finally, experimental evidence of the existence of these modes in extremely thin textured copper disks is also presented.